Readiness and Challenges of Indonesian Health Higher Education Independent Accreditation Institutions - Khalilah, Khalilah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research is intended to examine the readiness and challenges faced by the Indonesian Health Higher Education Independent Accreditation Institute (LAM-PTKes) as an independent accreditation institution with authority to carry out the accreditation of study programs in the science and health professions fields in Indonesia. Based on the case study method, LAM-PTKes generally has the infrastructure and resources to carry out its role as LAM which has the authority to accredit these study programs. The research results show that this institution still has two types of challenges. First, internal challenges include inadequate study program accreditation teams who can understand the technical aspects of accreditation and a need for more supporting IT staff who can help with the accreditation system of these study programs. Second, external challenges, namely the lack of understanding from field study program managers regarding the stages, processes, and documents needed in accreditation and the management system for accreditation supporting documents in general, still need to be better integrated. Despite these challenges, this institution strives to become an influential accreditation body in the national and global arena. To achieve this, this institution needs effective, adaptive and resilient accreditation management and an executive leadership team to manage accreditation issues developing in the digital era.